Measuring Misalignment Purchasing Power Parity and East Asian Currencies in the 1990's - Chinn, Menzie David (International Monetary Fund, 1999)
The concept of purchasing power parity (PPP) is used to evaluate whether eight East Asian currencies were overvalued on the eve of the 1997 crises. The Johansen and Horvath-Watson cointegration test procedures are applied to bilateral and multilateral exchange rates, deflated using CPIs, producer price indices (PPIs), and price indices of export goods. The second deflator yields the greatest evidence of "stationarity." The study find's that the Malaysian, Philippines, and Thai currencies were overvalued, while the Korean and Indonesian were substantially undervalued. Mixed results were obtained for the others. Measures of the equilibrium rate based on time trends in CPI-deflated rates typically suggest larger overvaluations